Examining the Relationship Between Financial Ratios and Stock Prices: A Case Study of IDX Banking Companies - Bahri, Syamsul; Fitri, Listia Nur; Nugraha, Aris Panca (Sean Institute, 2025)
This study aims to analyze the impact of financial ratios on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX). The variables examined include Current Ratio (CR), Return on Assets (ROA), Return on Equity (ROE), Price Earnings Ratio (PER), Price to Book Value (PBV), Earnings Per Share (EPS), and Debt to Equity Ratio (DER). This research employs a quantitative method with an explanatory design. The sample consists of 29 banking companies selected using the purposive sampling method, with an observation period from 2019 to 2023. Data analysis was conducted using multiple linear regression after passing classical assumption tests. The results show that ROA, ROE, PER, and DER significantly influence stock prices, while CR, PBV, and EPS have no significant effect. Simultaneously, all variables influence stock prices. The Adjusted R-Square value of 0.335 indicates that the studied variables explain 33.5% of stock price variations, while the remaining is influenced by other factors.